PELATIHAN PERHITUNGAN TITIK IMPAS SEBAGAI DASAR PERENCANAAN LABA USAHA PADA SISWA SMAN 20 KABUPATEN TANGERANG - Kurniawati, Herni; Ratna Niandra; Esther Dharmadi Santoso (Jurnal Serina Abdimas, 2025)
The goal of the community service program is to better teach SMA Negeri 20 Tangerang Regency students the science of accounting and economics, particularly as it relates to breaking even point analysis and profit forecasting. A business can use the break-even point to determine the minimum sales volume necessary to avoid losses while still failing to turn a profit (i.e., to make no profit at all). Furthermore, by indicating the level of sales that must be reached, the break-even point assists management in planning the required amount of profit. In order for students to benefit from this training, both those continuing their education in college (where the topic of break-even point is covered in a Management Accounting course) and those entering the workforce will be able to plan the business profitability of their place of employment. The data utilized in this Community service is primary data gathered directly from SMA Negeri 20 Tangerang Regency, specifically data from interviews with the principal and teachers discussing the urgency of the Accounting Economics material needed by students who will be used when they graduate from school. The Community service method consists of the following steps: (1) defining the break-even point and its components, which calculates the break-even point in terms of sales and units of goods; (2) calculating what elements make up the break-even point, which then calculates the break-even point in terms of units of goods; and (3) providing examples of questions related to the break-even point/BEP in order to help students understand/comprehend the break-even point/BEP. The crew did a great job doing this community service, which began on Thursday, October 03, 2024 at 10:00 WIB and ended at noon. The execution of Community service was carried out by visiting schools with students as part of Community service The executed community service program will eventually yield outcomes in the form of community service journals or proceedings. Furthermore, the extra outputs are loaded as extra outputs into HKI. ABSTRAK PKM dirancang untuk membantu siswa SMA Negeri 20 Kabupaten Tangerang memahami ekonomi akuntansi, terutama titik impas dalam merencanakan laba usaha. Titik impas membantu perusahaan merencanakan laba yang diinginkan dengan menentukan berapa banyak penjualan yang harus dilakukan agar perusahaan tidak mengalami kerugian tetapi juga belum memperoleh laba; dengan kata lain, titik impas menunjukkan berapa banyak penjualan yang harus dilakukan agar perusahaan tidak mengalami kerugian sama sekali. Dengan demikian, pelatihan ini bermanfaat bagi siswa-siswi yang sedang bekerja, karena mereka akan dapat merencanakan keuntungan bisnis tempat mereka bekerja. Mereka juga dapat melanjutkan studi mereka di universitas dengan mengambil mata kuliah akuntansi manajemen dengan topik titik impas atau BEP. Data yang digunakan dalam PKM ini berasal dari SMA Negeri 20 Kabupaten Tangerang secara langsung. Data ini diperoleh dari wawancara dengan guru dan kepala sekolah tentang seberapa penting materi ekonomi akuntansi bagi siswa untuk dipelajari setelah meninggalkan sekolah. Metode PKM terdiri dari (1) penjelasan teori atau konsep tentang titik impas, kemudian penjelasan tentang biaya tetap dan biaya variabel serta contohnya yang digunakan untuk menghitung titik impas/BEP; (2) menghitung komponen apa saja yang membentuk titik impas, kemudian menghitung titik impas dalam ukuran penjualan dan unit barang; dan (3) memberikan contoh soal yang berkaitan dengan titik impas/BEP dengan tujuan sederhana. PKM ini dijalankan oleh tim dengan baik dan lancar hingga selesai pada hari Kamis, 3 Oktober 2024 pukul 10.00 WIB. PKM dilakukan dengan mengunjungi sekolah bersama siswa. PKM yang telah dilaksanakan menghasilkan luaran dalam bentuk jurnal atau publikasi pengabdian masyarakat. Selain itu, luaran tambahan dimasukkan ke HKI.